Ontogenetic shifts in space use and habitat selection of tiger sharks (Galeocerdo cuvier) in The Bahamas - Kathryn A. Ayres; Austin J. Gallagher (PLoS ONE, 2025)
Tiger sharks (Galeocerdo cuvier) display notable variation in behavior, movement patterns, and habitat use, which reflects ontogenetic shifts in diet and access to habitat types. In this study, we analyzed a comprehensive five-year dataset (2018–2023) of acoustically tagged tiger sharks (n = 39) across two island regions in The Bahamas. Network analysis revealed life-stage-specific differences in space use and habitat selection, with a significant correlation between motility (measured as edge density within arrays) and shark size (fork length, FL). Generalized Additive Models (GAMs) indicated that female sub-adult tiger sharks (225–250 cm FL) exhibited broader and more interconnected movements than juvenile and mature sharks, which were closely associated with shallow seagrass habitats. For male tiger sharks, fork length showed a positive linear relationship with edge density. We estimated fork length at the time of first detection for analysis, rather than measurements taken at tagging, and emphasize the importance of this approach when examining ontogenetic patterns in tiger sharks, which exhibit rapid growth during early life stages. Additionally, adult, and sub-adult sharks were recorded at receiver stations along the east coast of the U.S., highlighting large-scale partial migratory behavior and reiterating the need for transboundary conservation strategies.